Hydraulic nutrient transport in a restored peatland buffer - Silvan, N.; Sallantaus, T.; Vasander, H.; Laine, J. (Boreal Environment Research Publishing Board, 2024)
The aim of this study was to investigate the hydraulic transport of nitrate (NO3–) and phosphate (PO43–) in a restored peatland buffer by quantifying the nitrate and phosphate input–output balance and nutrient transport in the buffer. The area of the buffer was ca. 0.5 ha, and it amounted to ca. 15%–25% of the water catchment area above. Nitrate and phosphate were added continuously during June–July in 1999, applying Ca(NO3)2 (110 kg Ca, 90 kg N ha–1) and K3PO4 (38 kg K, 30 kg P ha–1) water solution in the experimental area. Nutrient transport and retention in the buffer were monitored in the site in 1998–2001. Only ca. 0.5% of added nitrate and ca. 7% of added phosphate was leached through the buffer during the period 1999–2001. Especially added nitrate was retained in a relatively small area in the upper experimental area, ca. 0.2 ha, whereas added phosphate spread out to a much larger area. The results obtained indicate that the buffer is capable of removing effectively especially nitrate but also phosphate from throughflowing water, if the buffer area is large enough, and if the slope of the buffer is suitable.